2013
DOI: 10.1038/jid.2012.331
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 Inhibits the Melanogenesis of Normal Human Melanocytes through the JAK2–STAT6 Signaling Pathway

Abstract: Skin diseases can be characterized by their predominant CD4-positive T-helper (Th) cell profiles. Chronic dermatological conditions often give rise to abnormal skin pigmentation. To understand the role of Th cells in pigmentation, the effects of the major Th cell cytokines, IFNγ, IL-4, and IL-17A, on melanogenesis were evaluated using cultured normal human melanocytes (NHMs) instead of relying on transformed melanoma cell lines. IL-4 directly inhibited melanogenesis in NHMs and downregulated both transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…Of the pigmentation genes, DCT showed a drastic decrease of around 80%. Similar observations were also reported during the course of another study (17,18). TYRP1 and TYR were decreased to a lesser extent across different primary cultures treated with IFN-γ ( Fig.…”
Section: Ifn-γ Causes Cellular Hypopigmentation By Arresting Melanosomesupporting
confidence: 89%
“…Of the pigmentation genes, DCT showed a drastic decrease of around 80%. Similar observations were also reported during the course of another study (17,18). TYRP1 and TYR were decreased to a lesser extent across different primary cultures treated with IFN-γ ( Fig.…”
Section: Ifn-γ Causes Cellular Hypopigmentation By Arresting Melanosomesupporting
confidence: 89%
“…Kaempferol is a natural polyphenol compound that has been shown to specifically block IL-4-induced STAT6 phosphorylation through the selective inhibition of JAK3 activity [29]. The canonical pathway for IL-4 induced STAT6 phosphorylation typically involves JAK1 and JAK3 [30], though JAK2 can also participate (e.g., [31]).…”
Section: Resultsmentioning
confidence: 99%
“…In various dermatological conditions, including UV irradiation‐ and immune‐ and/or inflammation‐related disorders such as vitiligo, psoriasis and atopic dermatitis, keratinocyte‐derived paracrine factors can be involved in the regulation of melanogenesis, either by single action or combined effect within the intricate cytokine network …”
Section: Neighbouring Cellsmentioning
confidence: 99%
“…Neighbouring cells around melanocytes, such as keratinocytes, fibroblasts and immune cells, positively or negatively influence melanogenesis by secreting paracrine factors in response to UV irradiation or inflammatory conditions (Fig. ) . Furthermore, several studies have shown that extracellular matrix (ECM) proteins, which are responsible for structure formation and the transduction of cellular signalling pathways in the skin, can affect melanogenesis .…”
mentioning
confidence: 99%